Two novel ferrocenyl dipeptide‐like compounds generated via the Ugi four‐component reaction. Issue 8 (7th July 2015) - Shao, Guang‐Kui; Zhao, Mei; Wei, Zheng; Ma, Jian‐Ping; Guo, Dian‐Shun
<x xml:space="preserve">Abstract</x> The Ugi four‐component reaction, a powerful method for the synthesis of diverse dipeptide‐like derivatives in combinatorial chemistry, was used to synthesize (S)‐1′‐N‐[1‐(anthracen‐9‐yl)‐2‐(tert‐butylamino)‐2‐oxoethyl]‐N‐(4‐methoxyphenyl)carbamoylferrocene‐1‐carboxylic acid dichloromethane disolvate, [Fe(C6H5O2)(C33H31N2O3)]·2CH2Cl2, (I), and (S)‐2‐(anthracen‐9‐yl)‐N‐tert‐butyl‐2‐[N‐(4‐methylphenyl)ferrocenylformamido]acetamide, [Fe(C5H5)(C33H31N2O2)], (II). They adopt broadly similar molecular conformations, with near‐eclipsed cyclopentadienyl rings and near‐perpendicular amide planes in their dipeptide‐like chains, one of which is almost coplanar with its attached cyclopentadienyl ring but perpendicular to the aromatic ring bound to the N atom. In the supramolecular structure of (I), a two‐dimensional network is constructed based on molecular dimers and a combination of intermolecular O—H...O, N—H...O and C—H...O hydrogen bonds, forming R22(11), R22(16), R22(22) and C(9) motifs. These two‐dimensional networks are connected by C—H...O and C—H...Cl contacts to create a three‐dimensional framework, where one dichloromethane solvent molecule acts as a bridge between two neighbouring networks. In the packing of (II), classical hydrogen bonds are absent and an infinite one‐dimensional chain is generated via a combination of C—H...O hydrogen bonds and C—H...π interactions, producing a C(7) motif. This work describes a simple synthesis and the supramolecuar structures of ferrocenyl dipeptide‐like compounds and is significant in the development of redox‐active receptors.